Impact of Management Practices on Organisational Innovation in The Digital Age: A Study of the Manufacturing Industry in Malaysia - Rehman, Hafiz Mudassir; Au Yong, Hui Nee; Choong, Yuen Onn (UUM Press, 2021)
The manufacturing industry is an indispensable part of the economy, especially for Malaysia. The manufacturing sector in Malaysia is not only transforming raw material into products, but also contributing significantly to the country’s economy. Malaysia has attained a significant position in the world by exporting its manufactured goods. However, the production services always require innovation to meet the ever-changing customer demands. With the advent of Industry 4.0, the manufacturing industry faces constant challenges such as the innovation capability of organizations, and swift and frequent shifts in the use of technology. These issues may hamper the efforts of manufacturing firms to fully participate in Industry 4.0 Malaysia. Therefore, the objective of this study is to identify the influence of knowledge-oriented leadership, electronic human resource management (E-HRM), and decentralised organisational structure on organizational innovation. The current research has adopted a quantitative method to establish the relationship between these three variables and innovation in organizations. A total of 218 samples were collected from manufacturing firms located in Malaysia. Data collected through a self-administered questionnaire was examined by using SmartPLS software. The results of this research has added to the body of knowledge in the respective field by highlighting the significance of knowledge-oriented leadership and E-HRM in predicting organizational innovation. It can further help stakeholders to plan a way forward in facing Industry 4.0 through the development of innovation competencies.